2008
DOI: 10.1007/s10461-008-9462-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with HIV Testing Among Public Sector Clinic Attendees in Johannesburg, South Africa

Abstract: Uptake of VCT remains low in many sub-Saharan African countries. Men and women aged 15 and older were recruited from a family planning, STI, and VCT clinic in inner-city Johannesburg between 2004 and 2005 to take part in a cross-sectional survey on HIV testing (n = 198). Fourty-eight percent of participants reported previously testing for HIV and, of these, 86.9% reported disclosing their status to their sex partner. In multivariable analyses, individuals whose partners had been tested for HIV were more likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 23 publications
(28 reference statements)
4
52
1
Order By: Relevance
“…Like other studies, we found that men who perceived higher levels of HIV stigma in their networks were less likely to have HIV tested [35, 52]. This suggests that despite efforts to reduce HIV stigma in Tanzania, the negative influence of HIV stigma on testing persists [53].…”
Section: Discussionsupporting
confidence: 74%
“…Like other studies, we found that men who perceived higher levels of HIV stigma in their networks were less likely to have HIV tested [35, 52]. This suggests that despite efforts to reduce HIV stigma in Tanzania, the negative influence of HIV stigma on testing persists [53].…”
Section: Discussionsupporting
confidence: 74%
“…Persons who did not provide consent for HIV testing were wealthier and more educated [8587]. HIV stigma is also a well known barrier to uptake of HIV testing in general [8890]. Furthermore, longitudinal data from the Malawi Diffusion and Ideational Change Project (MDICP) showed that persons who tested positive for HIV and received their results were less likely to consent to repeat testing in subsequent waves of the survey [91], and failure to adjust for selection bias has been shown to yield underestimates of national HIV prevalence [87,92].…”
Section: Discussionmentioning
confidence: 99%
“…Misconceptions around serodiscordance are well-documented in South Africa (83,84), and commonly lead to the practice of testing by proxy (85), which precludes opportunities to reduce sexual risk-taking that accompanies awareness of serodiscordant status (86). Other concerning knowledge gaps identified included that almost half of women reported that a woman is protected from HIV if her partner is circumcised.…”
Section: Discussionmentioning
confidence: 99%